Spilling ink - Mazer Anne and Potter Ellen : 1953 and 1963; Anne Mazer and Ellen Potter (New York : Scholastic, 2010)
After receiving letters from fans asking for writing advice,accomplished authors Anne Mazer and Ellen Potter joined together to create this guidebook for young writers. The authors mix inspirational anecdotes with practical guidance on how to find a voice, develop characters and plot, make revisions, and overcome writer's block. Fun writing prompts will help young writers jump-start their own projects, and encouragement throughout will keep them at work.
O
830